Tindak Tutur Ekspresif Pembeli dalam Aplikasi TikTok - Masruri, Afiyah; Winda Hafifah, Apri; Fiamanillah, Fiamanillah; Fatmawati, Fatmawati (UIR Press, 2023)
This research was conducted because of the lack of expressive utterances used by consumers who often appear in the review column on the Tiktok application. The rating from this dare shop is usually far above, but it is possible that there are still many buyers who are not satisfied with the products offered. The reason for the buyer's dissatisfaction can be problems with the delivery of goods, the choice of type and the carelessness of the seller. This type of research includes quantitative analysis with analytical descriptive methods. The research used is buyer expressive speech acts data, which includes phrases, sentences, and words included in the TikTok review column for cosmetics stores. The source of the data in this sum is the cosmetics store TikTok @jennskin.naturals with screenshots. In this study, the data collection techniques used were reading and note-taking. There are three forms of expression found in the results of this study, namely thanking, apologizing and regretting. This explains the buyer's consideration for showing affection to the seller regarding the product purchased.